Study on Outcome based Education - Kumari, Sima (International Journal of Psychosocial Rehabilitation, 2020)
The researcher’s objective is to review and reconcile the research papers on outcome-based education in higher studies. The final result of higher education is being analyzed. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines have been used to analyse this paper. The Mixed Methods Appraisal Tool (MMAT) has been used to assess the selected research studies in terms of the quality of the research methodology. 19 related primary studies have been identified and analyzed since 2000. Such research illustrated outcome-based education in higher education.